Investigation of hydrodynamic determinants of competitive swimming strokes - Persyn, U.; de Maeyer, J.; Vervaecke, H. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
The underlying objective of this study was to help bridge the gap between practice and research. For that reason behavior patterns of the strokes from concrete modalities of movement were investigated. These patterns can be experienced personally by swimmers ar1d observed by others. The complete document (1974), parts of which are summarized here, does not provide for immediate application in practice. It will, however, form a sound basis for continued scientific research on the technical aspects of swimming. The study also focused on the problem of synchronization, which is perhaps the most complex area of research on hydrodynamic and technical determinants of human motion in water. Other components, ranging from simple to more complex, are buoyancy, resistance, propulsion, balance, and continuity of movemeni. It would have been simpler to start with less complex characteristics, but the possibility of integrating the results was a more important consideration.